Problem-based learning: The Maastricht know-how - Sargautytė, Rūta (Psichologija, 1999)
Critical perceptions and implications of the problem-based learning are discussed from the point of view of the participant of Summer-course at the University of Maastricht. Problem-based learning is a relatively new form of instruction with a long intellectual history. This approach of learning emerged in conjunction with the cognitive revolution in psychology. University of Maastricht uses this non-traditional system from his very founding in 1976. The principles of problem-based learning can be summarized as following: prior knowledge activation and elaboration through small-group problem analysis; the construction of problem-oriented semantic networks, including contextual cues derived from professionally relevant problems; and the fostering of epistemic curiosity. A number of studies provide empirical support for the assumptions underlying problem-based learning. The „seven jump" is an obligatory procedure for the analysis of each problem. Besides the professional knowledge and skills, the group discussion provides with the skills of more free communication.
Keywords: learning; problem-based learning; University of Maastricht